Kerangka Kerja Akuntansi Rumah Tangga Berbasis Islam Untuk Tenaga Kerja Wanita - Ramadhani, Febrina Nur; Anwar, Azwar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
This research aims to construct a household accounting framework for families of Indonesian women workers based on Islamic values. Using the Islamic Accounting Anthropology (IAA) methodology, this research involves four stages of analysis: existing, synchronic, diachronic, and construction. Data were collected through focus group discussions, interviews, observation, and documentation. The results showed that modernization brought foreign values, such as materialism and individualism, into rural households and influenced family members through communication. Written accounting is used by wives to monitor husbands' financial management. Synchronic analysis shows the continuity of local and religious values such as responsibility, cooperation and mutual respect, which are embodied in unwritten accounting practices. The diachronic analysis identified seven ideal Islamic values for household accounting: ikhtiar, ikhlash, tawakal, barakah, simplicity, kinship, and transparency. These values make up the basic household accounting equation expressed as Rizq + Barakah = Ikhtiar + Ikhlash + Tawakal. This basic equation guides the construction of household accounting through the integration of quantitative elements (income, expenditure, savings, investment) and qualitative elements (spiritual and ethical values). This framework serves as a means of worship and maintaining the trust entrusted by Allah